Opinions Of Iraqi College Students On Virtual English Classrooms - Abuther Omar Abdulaziz,; Mahdi Nadhim Baqer, (RES MILITARIS, 2022)
There are several adverse effects of the COVID-19 outbreak that is raging over the globe. The COVID-19 epidemic, on the other hand, increased interest in e-learning, which has been seen as a complementary medium in the educational process. The most efficient approach to learning new material and finishing academic assignments is face-to-face education and learning, which has long held this reputation. However, during the Covid-19 Pandemic, online education proved to be a helpful substitute. This study compares on-campus and online learning for EFL university students, examining preferences, efficacy, learning satisfaction, and obstacles. Data was gathered using quantitative techniques. To participate in the study, 45 undergraduate English as a Foreign Language (EFL) students from Imam Aadhem University College in Basra, Iraq, were chosen randomly (25 female and 20 male). The findings indicated that most students have a positive opinion of online education. Additionally, they liked online learning and thought it was more efficient. The results also showed that most students were satisfied with their education. The student's struggles with online assignments included internal and external ones, like difficulty focusing and opening cameras due to social issues.